MCSA/MCSE self-paced training kit (exam 70-291) implementing, managing, and maintaining a Microsoft Windows Server 2003 network infrastructure - Mackin, J. C. (Microsoft Press, 2003)
With the integrated system of skills-based tutorials and hands-on exercises in this official training kit, IT professionals learn how to administer and support the network infrastructure in Windows 2000 Professional and Windows 2000 Server--as they prepare for the corresponding MCP exam. The CD features a searchable version of the text.